2020
DOI: 10.4997/jrcpe.2020.306
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Prediabetes among Patients with Tuberculosis in a Single North Indian Tertiary Care Centre

Abstract: Background Prevalence of diabetes mellitus (DM), though believed to be high among patients with tuberculosis (TB), remains unclear for the want of systematic studies and unequivocal methods of diagnosing DM. This study was done to determine the prevalence of prediabetes and DM in adult patients with TB. Methods This prospective study of one year's duration, carried out at a tertiary care centre included 313 consecutive adult patients diagnosed (either microbiologically, histologically or based on clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The study showed that people with PTB were more affected by T2D or hyperglycaemia. The result was consistent with other epidemiological studies conducted in India, 25 , 26 , 27 Mexico 28 and Vietnam. 29 In these studies, the prevalence of diabetic patients with PTB and EPTB ranges from 15% to 35% and 8% to 26%, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The study showed that people with PTB were more affected by T2D or hyperglycaemia. The result was consistent with other epidemiological studies conducted in India, 25 , 26 , 27 Mexico 28 and Vietnam. 29 In these studies, the prevalence of diabetic patients with PTB and EPTB ranges from 15% to 35% and 8% to 26%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The result was consistent with other epidemiological studies conducted in India, 25‐27 Mexico 28 and Vietnam 29 . In these studies, the prevalence of diabetic patients with PTB and EPTB ranges from 15% to 35% and 8% to 26%, respectively 25‐29 . A cross‐sectional study conducted in Bangladesh also identified that PTB patients made eighty‐five per cent of the burden of diabetes in the TB population 14 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with a systematic review of 13 observational studies, DM was associated with an increased risk of PTB (relative risk = 3.11, 95% CI 2.27–4.26) 3 . In an Indian study, among the 313 PTB subjects, the prevalence of newly diagnosed DM and prediabetes was 32% and the overall prevalence of DM was 30% 4 . In Bangladesh, among the 1910 PTB patients who participated in screening for diabetes, 245 (12.8%) were found to have diabetes and 296 (15.5%) to have prediabetes 5 .…”
Section: Introductionmentioning
confidence: 98%